PELATIHAN APLIKASI BUDTRACK BERBASIS MOBILE UNTUK MONITORING BATAS WAKTU PENGGUNAAN OBAT DI KOTA TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Marfuah Marfuah; Masparudin Masparudin; Abdullah Abdullah; Samsudin Samsudin (LPPM Universitas Nusa Mandiri, 2026)
Public knowledge about the expiration time of medications is still limited, despite ongoing educational efforts. Many people rely solely on the Expiration Date (ED) on the primary packaging, which indicates the time limit for use after production. However, once the packaging is opened, the time limit no longer refers to the ED, but rather to the Beyond Use Date (BUD), which depends on the type of medication, its form, aroma, and color. The BUDTrack application not only facilitates the monitoring of the medication's expiration time but also educates the public regarding the expiration time based on both the ED and BUD. This aims to minimize losses and enhance awareness and adherence to avoid medication misuse. In addition to increasing public education on medication expiration time, it is also necessary to enhance the digital ecosystem in the health sector in Tembilahan. Therefore, it is important to measure the usability of the BUDTrack application using the System Usability Scale (SUS) method within the community, especially in Tembilahan, to evaluate the sustainability of the application’s implementation. The SUS calculation results from 34 respondents showed an average score of 77.3, indicating that the BUDTrack application falls within the Acceptable range, with a C grade scale and an adjective rating of